Historical Criticism of the Synoptic Gospels: (trans. Marcin Iwanicki, Joanna Klara Teske) - Alston, William; Iwanicki, Marcin; Teske, Joanna Klara (Roczniki Filozoficzne, 2023)
The original: “Historical Criticism of the Synoptic Gospels”, in “Behind” the Text: History and Biblical Interpretation, Scripture and Hermeneutics Series, red. Craig Bartholomew, C. Stephen Evans, Mary Healy, Murray Rae (Grand Rapids: Zondervan Academic, 2003), 151–179. Translation with the Publisher’s permission. This paper examines critically certain lines of argument used by many New Testament scholars to support their negative assessment of the reported sayings of Jesus and events in the Synoptic Gospels.